Detection performance of an X-band marine radar system for free-flying Asian particolored bats (Vespertilio sinensis) - Takahiro Sato; Yoichi Kawaguchi (PLoS ONE, 2025)
The rapidly growing number of wind farms is an increasing threat to many bat species and populations worldwide. Monitoring and prediction of bat collision risk requires techniques capable of quantifying bat movements over large spatial areas. Marine radar systems are highly effective tools for observing flying animals over large surveillance areas. However, the detection capability of marine radar systems has rarely been validated for bats. In this study, we sought to validate the effectiveness of a commercially available X-band marine radar in detecting Asian particolored bats ( Vespertilio sinensis ). To achieve this goal, we first examined the effect of adjusting the height of the radar antenna to reduce ground clutter. By lowering the antenna height from 2.2 m to 0.4 m, the visible area on radar images was increased by a factor of 2.1 over the entire 1.5 km observation range. Subsequently, we conducted radar observations under conditions where radar-detected targets could be reliably identified as bats. To acquire ground truth bat flight trajectories, we tracked bats at dusk using an ornithodolite simultaneously with radar scans. We manually tracked bat echoes on radar images and matched them to ornithodolite trajectories. Following this procedure, we identified 25 radar tracks as bat flights. These tracks were analyzed to determine the probability of echo detection (detection versus non-detection) as a function of distance from the radar by applying a generalized linear mixed model. The model analysis demonstrated that X-band marine radar was capable of detecting bat flights at a distance of up to 1.0 km, with a probability of detection exceeding 70%. Our results suggest that X-band marine radar can be an appropriate tool for monitoring bat movements, and also contribute to the establishment of range settings that should be considered for radar bat surveys.